Treatment outcomes among multidrug-resistant TB patients in Bahawal Victoria Hospital, Bahawalpur, Pakistan: a retrospective record review. (18th June 2020) - Atif, Muhammad; Ahmad, Wajiha; Ahmad, Nafees; Malik, Iram; Sarwar, Sajjad
Abstract: Background: This study aims to evaluate the treatment outcomes and factors associated with unsuccessful treatment outcomes among multidrug-resistant TB (MDR-TB) patients. Method: This was a retrospective observational study conducted at the Bahawal Victoria Hospital, Bahawalpur, Pakistan. The sociodemographic, clinical and treatment-related data of MDR-TB patients registered at the study site between June 2014 and December 2016 were retrospectively collected. Patients' treatment outcomes were categorized on the basis of WHO-recommended criteria. Multivariate binary logistic regression analysis was used to find the independent factors associated with unsuccessful treatment outcomes. Results: Out of 179 MDR-TB patients, 106 (59.2%) completed their treatment successfully. The remaining 73 patients (40.8%) had unsuccessful treatment outcomes, among whom 45 (25.1%) died, while 18 (10.1%) were lost to follow-up. Factors associated with unsuccessful treatment outcomes included age ≥40 y (AOR 4.310; p = 0.006), unsuccessful interim treatment outcomes (AOR 5.810; p = 0.032), occurrence of adverse events (AOR 0.290; p = 0.029) and ofloxacin resistance (AOR 2.952; p = 0.042). Conclusion: The treatment success rate among the selected cohort of MDR-TB patients was less than the target of ≥75% set by the WHO in the End TB Strategy. The lower treatment success rate at the study site requires urgent attention from clinicians and program managers.